The impact of green marketing practices on consumer buying decision - Fonseca, Joana Cristina Gamboia (2015)
Color can be one of the most important characteristics to impulse customers to buy certain products. So, organizations have been using green marketing practices, as transforming products into more friendly for the environment and incorporating features which cause the less impact in it. These products are emerging as differentiating products, in order to follow up with these value-conscious customers, whose consumptions patterns and buying-decision have been evolving. Customers have become more and more concerned with environmental issues and they want to have an active role in order to diminish the impact their actions have in the environment. There is no possible way the earth has the ability to sustain itself. Therefore, it requires customers and organizations interaction and contribution for protecting it and the awareness of environmental issues, such as global warming, currently affecting every individual on earth. Corporate social responsibility is another topic which refers to the organizations’ responsible actions in society, offering and marketing products which can be less hazard for the environment. Therefore, the purpose of this research is to investigate the customers’ perception on organizations attitudes when these engage in green marketing practices, and also how it affects and, in ways, shapes customers buying-decision when aware of the impact of their actions in the environment. This study was based on the literature review and it was conducted a questionnaire to 250 customers. The analysis of the results show customers tend to be influenced by green marketing practices and are more motivated when aware of the environmental issues. However, customers are still not very clear about companies’ intentions, when engaging into these approaches